An APPLICATION OF BALANCE SCORECARD AND ACCOUNTING INFORMATION SYSTEM TO INVESTMENT DECISION-MAKING THROUGH COMPANY PERFORMANCE ASSESSMENT - pramadhan, Aswar (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
This research aims to analyze the influence of the Balance Scorecard and accounting information systems on investment decision making through assessing company performance. The Balance Scorecard as a performance management tool provides a comprehensive view of financial and non-financial aspects that are relevant for investment decision making through assessing company performance, while the accounting information system supports the decision making process by providing accurate and relevant information. . The research results show that the KPI (Key Performance Indicator) Balance Scorecard and accounting information system indicators have a significant influence on Investment decision making, while Performance Assessment alone is not able to mediate the Balance Scorecard and accounting Information System in Investment Decision Making. Because the Balance Scorecard is the Balance Scorecard as Performance management tools provide a comprehensive view of financial and non-financial aspects relevant for investment decision making, while accounting information systems support the decision making process by providing accurate and relevant information. These findings indicate that the implementation of the KPI Balance Scorecard and effective accounting information system indicators can improve the quality of investment decisions to be more accurate and comprehensive. The implications of this research support the importance of integrating these two tools in strategic decision making practices in companies. Keywords : Balance Scorecard, Accounting Information System, Company Performance Assessment, and Investment Decision Making.